A quantitative study on the relationship between learning style and English-speaking skill - Zumrudiana, Ainu; Alejandro, Francisco Diaz (Early Publishing Group, 2025)
This study examines the relationship between individual learning styles and English-speaking skills, a critical area in language education given the importance of speaking proficiency for effective communication. Recognizing that learners’ preferred modalities—visual, auditory, kinaesthetic, and reading/writing—may influence their ability to produce spoken English, this research contributes to the ongoing discourse on personalized language teaching strategies. While previous studies have suggested a connection between learning styles and language performance, there remains a paucity of empirical, statistically robust evidence specifically addressing speaking skills. This research aims to fill this gap by exploring the extent to which different learning styles predict speaking proficiency among university students. Employing a correlational research design, the study involved 120 undergraduate students enrolled in an English language program at an Indonesian public university. Data were collected through two instruments: a VARK questionnaire to determine dominant learning styles and a standardized speaking rubric aligned with the Common European Framework of Reference for Languages to assess speaking performance. Participants completed the questionnaires and performed speaking tasks under controlled conditions, with their performances rated independently by trained raters who were blind to their learning style profiles. Data analysis involved descriptive statistics and Pearson correlation coefficients to examine the relationship between each learning style and speaking scores. The results revealed significant positive correlations for visual and auditory learning styles, indicating that learners who prefer these styles tend to perform better in speaking tasks. The findings suggest that aligning instruction with learners’ preferred modalities can enhance speaking proficiency. This study underscores the importance of incorporating diverse teaching strategies tailored to learners' preferences to optimize speaking development. The implications advocate for language educators to utilize multimodal approaches that cater to different learning styles, thereby fostering greater engagement and improving speaking outcomes among students